Heparin-Binding Hemagglutinin-Induced Trained Immunity in Macrophages: Implications for Antimycobacterial Defense - Yongqiang Li; Xiuping Jia; Jinhua Tang; Huilian Qiao; Jiani Zhou; Yueyun Ma (Biomolecules)
Tuberculosis (TB) is a major global health threat, with the current Bacillus Calmette–Guérin (BCG) vaccine having limited efficacy against adult pulmonary disease. Trained immunity (TI) is a form of innate immune memory that enhances antimicrobial defense. It is characterized by the epigenetic and metabolic reprogramming of innate immune cells and holds promise as a promising approach to prevent TB. In this study, we investigated the capacity of heparin-binding hemagglutinin (HBHA), a methylated antigen of Mycobacterium tuberculosis, to induce TI in murine RAW264.7 macrophages, human-derived THP-1 macrophages, and human peripheral blood mononuclear cells (hPBMCs). HBHA-trained macrophages exhibited the enhanced expression of pro-inflammatory cytokines (IL-1β, IL-6, TNF-α) following secondary lipopolysaccharide stimulation. The epigenetic profiling indicated elevated levels of H3K4me1 and H3K4me3 histone marks at cytokine gene loci. Further, metabolic analysis revealed heightened lactate production and the increased expression of glycolytic enzymes. Functionally, HBHA-trained macrophages exhibited improved control of intracellular mycobacteria, as evidenced by a significant reduction in colony-forming units following BCG infection. These findings elucidate that HBHA induces a functional TI phenotype via coordinated epigenetic and metabolic changes, and suggest HBHA may serve as a valuable tool for studying TI and its relevance to host defense against mycobacterial infections, pending further in vivo and clinical validation.